Sensitivity of color Doppler sonography: an experimental approach - Delorme, Stefan; Kaick, Gerhard van (Ultrasound in medicine & biology, 1999)
The purpose of this study was to estimate the size required for small vessels to become detectable with color Doppler sonography. A murine experimental tumor was examined with color Doppler sonography after injection of 1.5 mL of the contrast medium Levovist®. Histologically, we measured vessel diameters inside the tumor, as well as in its direct neighborhood. With color Doppler at a transmit frequency of 7 MHz, vessels were only detected in the tumor’s environment, but not inside. By histology, the 95% quantile of the vessel diameter distribution was found to be 21 μm inside the tumor, 37 μm in the underlying muscle, and 73 μm in the directly adjacent connective tissue. Vessels in the upper range of the size distribution in the muscle and connective tissue are probably detectable. Using the 95% quantile as an estimate, and correcting the values for possible shrinkage, using a factor of 1.91 reported in the literature, vessels in the 74-134 μm range may be detected under the given conditions, whereas vessels measuring 38 μm or less are inaccessible to color Doppler.
Gesehen am 18.02.2021